DUKUNGAN PEMERINTAH JEPANG KEPADA PEMERINTAH INDONESIA PADA SEKTOR PERTANIAN MELALUI KERJASAMA ECONOMIC PARTNERSHIP AGREEMENT (EPA) TAHUN 2006-2010 - Fitri Kusuma Wardhani (2014)
From an economic perspective, Indonesia is now included in the category of third world countries or developing countries who are trying to align with the developed countries. One of the Indonesia's efforts is establishing economic cooperation with several countries including Japan. Before Negotiations of Economic Partnership Agreement between Indonesia and Japan, they are already cooperated in the economics cooperation through Official Development Assistance scheme (ODA). Through ODA, Japan has supported Indonesia in financial trouble. However, entering the era of the 2000s, Japan is no longer relying on assistance through ODA scheme, but more emphasis and has shifted through a cooperation strategy of FTA (Free Trade Agreement) or EPA (Economic Partnership Agreement). Both type of assistance have different objectives. ODA goal is to reduce the cost of investment of Japanese firms in ODA recipient countries. While the EPA goal is to ensure the energy supply in the long term.